Foreign Body in the Oral Cavity Mimicking a Benign Connective Tissue Tumor. (24th March 2013) - Puliyel, Divya; Balouch, Amir; Ram, Saravanan; Sedghizadeh, Parish P.
Abstract : Foreign bodies may be embedded in the oral cavity either by traumatic injury or iatrogenically. The commonly encountered iatrogenic foreign bodies are restorative materials like amalgam, obturation materials, broken instruments, needles, and impression materials. This paper describes an asymptomatic presentation of a foreign body in the oral mucosa which clinically appeared like a benign connective tissue tumor.